The Prison Reality in Ecuador, Survival, Social Discarding of Human Beings or Comprehensive Rehabilitation - Verdugo Lazo, Jorge Eduardo (2023)
The Ecuadorian prison system has been in crisis, with no definitive solution currently in sight, both structurally and in terms of people’s human rights deprived of liberty. The State punitive power exercise has focused on the use of prison as a privileged mechanism, ignoring alternative practices that could better ensure human rights and rationalize the execution of the sentence, for which the application of a multidisciplinary approach that addresses a multicausal problem such as the crisis in the prison systemthat can be understood as a reflection of social conflict and the struggle between the State and criminal groups. The fundamental aspects related to these ideas are analyzed in this article, based on a documentary and statistical review of the current situation that allows us to foresee a more complex future if appropriate measures are not adopted to guarantee the system’s functionality and the citizens’ rights deprived of liberty.